Kineto-static Analysis of Planetary Gear Train based on Vector Bond Graph Method - Wang Zhongshuang; Jing Weike (Jixie chuandong)
For the problem of kineto- static analysis for planetary gear train,the corresponding vector bond graph procedure is proposed. Based on the kinematic constraint condition of planar compound revolute joint,the procedure for modeling planar compound revolute joint by more concise vector bond graph is described. From the kinematic constraint relations of components of planetary gear train,the corresponding vector bond graph model of such system is built by assembling the vector bond graph model of tie rod,planetary gear,compound revolute joint and gear pair. By the effective augment method,the differential causality in the vector bond graph of such system is eliminated. By the corresponding algorithm,the computer aided modeling and dynamic analysis of planetary gear train system with double planetary gear is realized,the validity of the procedure proposed is illustrated.